Blockchain-basiertes virtuelles Geld - Spiegel, Alexandra (Mohr Siebeck, 2020)
Blockchain-based means of payment raise questions in respect of monetary theory as well as their practical use by legal entities. Taking the best-known example of virtual money Bitcoin to illuminate the issue, Alexandra Spiegel looks at the legal situation in France, China, and the UK in her comparative study.
PublicationDate: 20200826
Keywords: Dialectical Theology -- Bitcoins -- Kryptowährung -- smart contracts -- distributed ledgers -- Bitcoin -- mitgliedschaftliche Legitimation -- Grundrechtsverzicht -- Geldbegriff -- Bürgerliches Recht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Internationales Privatrecht